Sistem Keamanan Brankas Berbasis Mikrokontroller Atmega 328 Dengan Munggunakan Kode One Time Password (OTP) - M Zurairah; M Adam; P Harahap; Zaharuddin (Jurnal MESIL (Mesin Elektro Sipil), 2022)
The technological development of a security system really needs to be considered, especially for the security system for storing valuables and other important documents such as safes. In general, safes or safety cabinets that exist today do not have a good security system and the use of combination numbers seems impractical in accessing them because it takes a long time to find the right number. Arduino is a single board microcontroller (or more easily called a microcontroller kit) developed by arduino.cc. the nature of this arduino itself is open-source so it is free to use and distribute. The purpose and benefit of this research is the development of the era in this modernization era, microcontroller technology is expected to be able to perform a security system as the use of electronic devices to replace conventional key security systems. The components used include Radio Frequency Identification (RFID), SIM800L and Magnetic Switch Sensors.